2018
DOI: 10.1159/000486933
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances in Treatment Strategies for Lupus Nephritis

Abstract: Systemic lupus erythematosus (SLE) is an autoimmune chronic inflammatory disease that affects multiple organs and tissues. Lupus nephritis (LN) is a serious complication of SLE, which occurs at a high rate. Conventional treatment strategies of LN have been widely accepted by two concepts such as induction therapy and maintenance therapy. In LN induction therapy until recently, cyclophosphamide in combination with prednisone (PSL) has been the standard method of treatment for proliferative forms of LN. In the l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…The depletion of B cells with anti-CD20 antibodies (the mouse equivalent of rituximab) [60] and mycophenolate mofetil (MMF) [11] attenuated hypertension in this mouse model. Importantly, both rituximab and MMF are used clinically in human patients with SLE [61, 62] and MMF has been shown to reduce blood pressure in small clinical studies in humans [63]. A more recent study from our laboratory addressed the question of whether autoantibodies mechanistically contribute to the pathogenesis of hypertension during autoimmune disease.…”
Section: Introductionmentioning
confidence: 99%
“…The depletion of B cells with anti-CD20 antibodies (the mouse equivalent of rituximab) [60] and mycophenolate mofetil (MMF) [11] attenuated hypertension in this mouse model. Importantly, both rituximab and MMF are used clinically in human patients with SLE [61, 62] and MMF has been shown to reduce blood pressure in small clinical studies in humans [63]. A more recent study from our laboratory addressed the question of whether autoantibodies mechanistically contribute to the pathogenesis of hypertension during autoimmune disease.…”
Section: Introductionmentioning
confidence: 99%
“…Complement is implicated in the pathogenesis of SLE, and C3c, a marker of intra glomerular complement activation in MRL/lpr mice, is deposited in the kidney during lupus nephritis (Karasawa et al, 2018). Our results showed that INK128 significantly reduced the deposition of complement factor C3c, but rapamycin showed slight effects in kidney (Figure 1F).…”
Section: Resultsmentioning
confidence: 61%
“…However, in the early stages of LN including class I and II, no therapy is recommended by the American College of Rheumatology (ACR) guideline. The European LeagueAgainst Rheumatism and European Renal Association-European Dialysis and Transplant Association (EULAR/ERA-EDTA) suggested low to moderate doses of oral steroid agents which cause moderate proteinuria and glomerular hematuria [ 18 , 41 , 46 , 47 ]. It should be noted that 5–20% patients with LN even with immunosuppressive therapy develop ESRD within 10 years [ 43 ].…”
Section: Resultsmentioning
confidence: 99%